Antibacterial Activity of Different Varieties of Curcuma longa Rhizome Extracts Against Pathogenic Bacteria - Naz, Shagufta; Akbar, Irum; Ilyas, Saiqa; Jabeen, Safia (Asian Journal of Chemistry, 2012)
Curcuma longa rhizome extracts of different samples (A, B and C) were evaluated for antibacterial activity against four pathogenic bacterial strains, which are Bacillus subtilis, Bacillus macerans, Bacillus licheniformis and Azotobacter sp. using agar well diffusion method. The different solvents used to determine antibacterial activity were ethanol, hexane, ethyl acetate, butanol and water. Ethanol, hexane and ethyl acetate extracts exhibited antibacterial activity as indicated by minimum inhibitory concentration (MIC) values, but other extracts of butanol and water did not show any antibacterial activity. Ethanolic extract of all samples is most active against all pathogens. Hexane and ethyl acetate soluble extract of all samples exhibit most promising antibacterial activity. Hexane and ethyl acetate extracts of sample B were the most resistant against B. licheniformis and Azotobacter respectively. Among all the samples, the ethanolic extract of sample C (Kasur variety) was found to be the most effective against all tested strains. The minimum inhibitory concentration values of different strains, extracts and varieties ranged from 0.01-0.83 mg/mL.